Idiopathic Non-Puerperal Uterine Inversion in a Young Female: A Case Report - Amit Kumar; Vinod Kumar; Priyam Sharma (Case Reports in Clinical Practice)
Non-puerperal uterine inversion (NPUI) is an extremely rare condition. Our case is the second, where a young female (adolescent age group) presented with uterine inversion, and is the first without any identifiable cause of uterine inversion. Her chief complaints were chronic menorrhagia, abdominal pain, and episodes of acute urinary retention. Most of the reported cases have identifiable etiology for the inversion. The reporting of this case is worthwhile because of its rarity in such age groups and even without any defined cause (spontaneous occurrence), making the diagnosis of uterine inversion in this condition challenging, particularly in this very young age. In our case, she was initially misdiagnosed as having a cervical polyp clinically and radiologically, especially on ultrasonography (USG). Finally, it was diagnosed as uterine inversion by magnetic resonance imaging (MRI) of the pelvis and retrospective evaluation of USG. Magnetic resonance imaging (MRI) thus plays a pivotal role in the diagnosis of uterine inversion. Treatment of uterine inversion is either mostly by manual repositioning, and if not possible, surgery is contemplated.